Pengaruh Kinerja Karyawan Unit Tata Usaha Terhadap Pengelolaan Arsip di Rumah Sakit X - Lukitasari, Arnandita Eka; Goenarso, Roberto; Kurniawan, Afif; Mamesah, Marline Merke (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Archive management is not just storing or accumulating files, but requires a system or process for storing them, which starts with organizing and grouping files according to their type and use. Problems often arise when organizations do not take structural steps for archiving, in this case HR plays an important role in it. The purpose of this study was to analyze the performance of administrative unit employees on archive management at RSAHK. The collection technique used was through observation, interviews, focus group discussions (FGD) with open questions through discussion group and documentation. The obstacles experienced by this administrative unit related to the creation of archives were caused by the process of making letters, starting from the concept until the letter received approval and then it could be sent to the destination address of the letter. The results of this study were obtained from the quantity of work which includes a discrepancy between educational background and jobdesk with the number of employees in this unit so that it affects the process of making letters which has an impact on reducing achievement indicators in the period January - March 2023. It was found that there was an influence on the performance of administrative unit employees on archive management, so that training was needed to support the quality of service in the administrative unit and conduct regular evaluations to keep monitoring the performance of existing employees.